2014
DOI: 10.1097/dcr.0000000000000087
|View full text |Cite
|
Sign up to set email alerts
|

Combined Aluminum Potassium Sulfate and Tannic Acid Sclerosing Therapy and Anal Encirclement Using an Elastic Artificial Ligament for Rectal Prolapse

Abstract: This procedure is quick and easy to perform, with no formidable morbidity, and the recurrence rate is reasonably low. Therefore, it seems to be a reasonable alternative for rectal prolapse in frail, elderly, and high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Sclerosants including ethanolamine oleate, [40] quinine, [41] hypertonic saline, [42] 5% phenol, [43] An's Shaobei injection, Xiaozhiling injection, [44] potassium aluminum sulfate and tannic acid, [45][46][47][48] have been used for the sclerotherapy of grade I-II internal hemorrhoids. ASCRS recommends 5% phenol dissolved in almond oil, vegetable oil or sodium tetradecyl sulfate in ASCRS Clinical Practice Guidelines for Hemorrhoid Management 2018.…”
Section: Endoscopic Sclerotherapymentioning
confidence: 99%
“…Sclerosants including ethanolamine oleate, [40] quinine, [41] hypertonic saline, [42] 5% phenol, [43] An's Shaobei injection, Xiaozhiling injection, [44] potassium aluminum sulfate and tannic acid, [45][46][47][48] have been used for the sclerotherapy of grade I-II internal hemorrhoids. ASCRS recommends 5% phenol dissolved in almond oil, vegetable oil or sodium tetradecyl sulfate in ASCRS Clinical Practice Guidelines for Hemorrhoid Management 2018.…”
Section: Endoscopic Sclerotherapymentioning
confidence: 99%
“…5,6 ALTAS is not currently approved by the US Food and Drug Administration; however, it is used throughout Asia and has been applied in the treatment of rectal prolapse and rectocele. 1,8,9 Most of the previous trials regarding ALTAS have reported on its short-term outcomes. There are few reports of the long-term results of ALTAS, with the longest period of study being 5 years.…”
mentioning
confidence: 99%
“…Injection sclerotherapy is indicated for hemorrhoids and rectal prolapsed. It is minimally invasive and economical, but seldom used to treat rectocele [ 33 ]. ALTA treatment interrupts the blood flow to the hemorrhoids resulting in sporadic hemostatic effect and contraction of hemorrhoids.…”
Section: Discussionmentioning
confidence: 99%